PENINGKATAN DAYA SAING USAHA MIKRO PEMPEK IKAN DAN NABATI SAYURAN TROPIS DI KOTA MALANG - Nugroho, Yuni Agung; Sugiarti, Untung (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
Community Development Activities (IbM) is designed to address the problems faced by partner companies. The implementation of IbM will be carried out by the following methods: a) Transfer of Application of Sanitation and Hygiene Standard to Pempek Production, c) Management training, financial management of production and marketing management, d) Monitoring and Evaluation. The results of IbM activities that have been done is the aid of mixing machine pempek dough dedicated to Partners 2, while for Part 1 in the form of fretrer polytron and vacum sealer. However, the pempping stirrer can be used, after the electric power of partner 2 plus the power to 1300 watts. Mitra 1 (Pempek Maliana) is more open and creative in developing pempek products, while partner 2 (Pempek Sulfat 28) still adheres to pempek that already exist in Malang with the same appearance and hard. Assistance and counseling to open insight and add skills have been done but at Partner 2 is still not able to adopt it. Partner 1 is already more advanced in terms of innovation and creativity in products and marketing.Keywords: competitiveness, micro business, pempek, tropical vegetables